Solid inclusion complex of terpinen‐4‐ol/β‐cyclodextrin: kinetic release, mechanism and its antibacterial activity. (19th December 2014) - Yang, Zujin; Xiao, Zuobing; Ji, Hongbing
Abstract Terpinen‐4‐ol has several biological properties, but its low stability and water‐solubility limit its use. This study reports the formation of a solid terpinen‐4‐ol/β‐cyclodextrin (β‐CD) inclusion complex via lyophilization. Release experiments were performed at various temperatures (40, 60, 80, and 100°C) with humidity of 70%. The release of terpinen‐4‐ol was significantly increased with rising temperature. Avrami's equation was used to analyse release kinetics and a good fit was observed for terpinen‐4‐ol release. In addition, the complex enhanced antibacterial activity against Staphylococcus aurueus, Pseudomonas aeruginosa and Escherichia coli, with concentration ranging from 1.25 mg/ml to 5 mg/ml. To explain the experimental data, physico‐chemical techniques have been utilized to investigate the inclusion complex of terpinen‐4‐ol with β‐CD. Finally, the possible structure of the complex was proposed by quantum chemical calculations. The results indicated that enhanced thermal stability and antibacterial activity of terpinen‐4‐ol could be attributed to the weak interactions of hydrogen bonds between terpinen‐4‐ol and β‐CD. Copyright © 2014 John Wiley & Sons, Ltd.